The Little Green Data Book 2009 - World Bank (World Bank, 2012)
The 2009 edition of the little green data book includes a focus section, four introductory pages that focus on a specific issue related to development and the environment. This year the focus is on urban areas and the environment, exploring how cities and climate change are affecting the way we live and how good public policies can improve prospects for future generations. Urbanization and economic growth move in tandem. As emerging market economies develop, they increase their contribution to greenhouse gas emissions. The emissions of developed and developing country economies together increase the vulnerability of cities to climate change. Cities are particularly vulnerable to climate change impacts because they concentrate people, infrastructure, and economic activity. But good public policies can reduce greenhouse gas emissions and other pollutants while minimizing the impacts from climate change.